American photography - Orvell, Miles (Oxford University Press, 2003)
150 years of American photography come alive in this exciting new book, placing it in its cultural context for the first time. Orvell examines this fascinating subject through a wide range of well known and less-well known images. He ranges from portraiture and landscape photography, family albums and memory, and analyses the particularly 'American' way in which American photographers have viewed the world around them